2014
DOI: 10.1039/c3mb70588a
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of candidate disease genes by enlarging the seed set and fusing information of the network topology and gene expression

Abstract: The identification of disease genes is very important not only to provide greater understanding of gene function and cellular mechanisms which drive human disease, but also to enhance human disease diagnosis and treatment. Recently, high-throughput techniques have been applied to detect dozens or even hundreds of candidate genes. However, experimental approaches to validate the many candidates are usually time-consuming, tedious and expensive, and sometimes lack reproducibility. Therefore, numerous theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…According to the probability that the walker would reach the node after the RWR enters the stable state, nodes ranked top 10 are held as candidate DmMGs. Previous studies suggested various ways to select candidate nodes including using the most accessible node (i.e., top 1) [58, 59], top 5 [60], top 10 [61,62], top 20 [62], and top 100 nodes [63], but no consensus rules have been proposed. In this work, we retained the top 10 accessible nodes to keep a balanced tradeoff between choosing too few informative genes (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…According to the probability that the walker would reach the node after the RWR enters the stable state, nodes ranked top 10 are held as candidate DmMGs. Previous studies suggested various ways to select candidate nodes including using the most accessible node (i.e., top 1) [58, 59], top 5 [60], top 10 [61,62], top 20 [62], and top 100 nodes [63], but no consensus rules have been proposed. In this work, we retained the top 10 accessible nodes to keep a balanced tradeoff between choosing too few informative genes (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…All of these methods depend on the topological structure of the interactome; but, while linkage and neighbourhood based methods rely upon a particular topological metric, such as pairwise or nearest interactions, diffusion based methods adopt the full information of the network topology. Diffusion-based methods have been recently applied and shown to achieve the state-of-the-art predictive performance [12] , [13] , [14] , [15] ; in addition, combining predictions made by different methods in a 'consensus method' yielded to Pareto optimal performance in the precision-recall objectives [15] .…”
Section: Resultsmentioning
confidence: 99%
“…This set contained 123 unique genes. These databases which were source of the gene set 2 were used as the evaluation set in other studies for gene prioritization [18-20]. …”
Section: Methodsmentioning
confidence: 99%